Language policies and teacher strategies for promoting psychological inclusiveness in the diverse classroom in Aba aducation zone - Emmanuel lucas Nwachukwu; Francisca Ifeoma Ehiemere; Osuji Columbus Otuosorochi; Regina Ijeoma Ukwuoma (Journal of Language and Pragmatics Studies, 2026)
This study examined the influence of language policies on classroom inclusivity and the strategies employed by teachers to promote psychological inclusiveness in linguistically diverse secondary school classrooms in Aba Education Zone, Abia State, Nigeria. A descriptive survey design was adopted. Using stratified random sampling, 200 junior and senior secondary school teachers were selected. Data were collected via a structured four-point Likert-scale questionnaire and analyzed using descriptive statistics and inferential statistics (independent samples t-test; one-way ANOVA) at α = 0.05. Language policies exerted limited practical influence on psychological inclusiveness (cluster mean = 2.48), revealing a persistent policy-practice gap. Teachers nonetheless employed diverse inclusive strategies including differentiated instruction, code-switching, and culturally responsive pedagogy (cluster mean = 2.79). Key implementation barriers included inadequate training, resource deficits, and weak administrative support (cluster mean = 2.67). No statistically significant differences in inclusive strategy use were found by gender (t = 0.743, p = .458) or teaching experience (F = 1.032, p = .380). This study contributes empirical evidence on the disconnect between language policy intent and classroom reality in a linguistically complex Nigerian urban zone, offering actionable insights for policymakers, curriculum designers, and teacher educators.